2010
DOI: 10.1063/1.3469810
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of O2 sticking on Pt(111) using the ab initio based ReaxFF reactive force field

Abstract: The molecular dynamics technique with the ab initio based classical reactive force field ReaxFF is used to study the adsorption dynamics of O(2) on Pt(111) for both normal and oblique impacts. Overall, good quantitative agreement with the experimental data is found at low incident energies. Specifically, our simulations reproduce the characteristic minimum of the trapping probability at kinetic incident energies around 0.1 eV. This feature is determined by the presence of a physisorption well in the ReaxFF pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 39 publications
6
44
0
Order By: Relevance
“…The use of such a reaction specific RFF allowed for obtaining, from classical trajectory calculations, sticking probabilities in good overall agreement with previous state-of-the-art theoretical results and experiments. Interestingly, only a few months later, Valentini et al [51] also reported classical trajectory MD results in good agreement with molecular beam experiments for O 2 /Pt(111), using a ReaxFF PES specifically trained to reproduce a large set of O/Pt(111) and O 2 /Pt(111) DFT interaction energies (including molecularly adsorbed states and dissociation barriers) [51].…”
Section: Introductionmentioning
confidence: 84%
“…The use of such a reaction specific RFF allowed for obtaining, from classical trajectory calculations, sticking probabilities in good overall agreement with previous state-of-the-art theoretical results and experiments. Interestingly, only a few months later, Valentini et al [51] also reported classical trajectory MD results in good agreement with molecular beam experiments for O 2 /Pt(111), using a ReaxFF PES specifically trained to reproduce a large set of O/Pt(111) and O 2 /Pt(111) DFT interaction energies (including molecularly adsorbed states and dissociation barriers) [51].…”
Section: Introductionmentioning
confidence: 84%
“…Forces on the atoms are derived from the ReaxFF potential [18]. This force field has now been successfully applied to describe nearly half of the periodic table of the elements and their compounds, including hydrocarbons [18,37], metals and metalcatalyzed reactions [38,39], metal oxides [40], metal hydrides [41] and silicon and silicon dioxide [42][43][44]. Recently, it has also been used for organic molecules, such as glycine [19,45], as well as for complex molecules, such as DNA [46].…”
Section: Interatomic Potentialmentioning
confidence: 99%
“…This issue is especially apparent in low-density gas phase simulations, where EEM-ReaxFF predicts small, but certainly nonzero, charges on isolated molecular species, which significantly affects accommodation coefficients. 135 In simulations of dense systems, unrealistic charge-transfer may also occur (e.g., between two dielectric phases with a different intrinsic electronegativity). To ameliorate this issue, we have recently incorporated atom-condensed Kohn-Sham DFT approximated to second order (ACKS2) in ReaxFF.…”
Section: Future Developments and Outlookmentioning
confidence: 99%